1991
DOI: 10.1111/j.1365-2826.1991.tb00318.x
|View full text |Cite
|
Sign up to set email alerts
|

Oxytocin Excites Neurons Located in the Ventromedial Nucleus of the Guinea‐Pig Hypothalamus

Abstract: The area of the ventromedial nucleus of the hypothalamus in the guinea-pig was shown in autoradiographs to contain high affinity binding sites for oxytocin. In order to ascertain whether these sites may represent neuronal receptors, single-cell extracellular recordings were obtained from ventromedial neurons in coronal slices of t h e hypothalamus of adult guinea-pigs. Oxytocin applied in the nanomolar range excited about half of the neurons tested; none were inhibited. The response to the peptide was reversib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

1992
1992
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 36 publications
(21 reference statements)
1
2
0
Order By: Relevance
“…Perfusing a mixture of 400nM (each) OXT plus AVP or individually administering these peptides elicited strong (ΔF/F ∼500-600%) responses in VMHvl Esr1 cells (Figure 1Fii and Supplemental Figure S1F-G). These findings demonstrated the presence of functional AVP and OXT receptors in VMHvl Esr1 neurons, consistent with prior electrophysiological studies in mice and guinea pigs 71,72 . Furthermore, it established a system for evaluating cellular responses to OXT and AVP following CRISPR/Cas9 based mutations of their receptors.…”
Section: Resultssupporting
confidence: 90%
“…Perfusing a mixture of 400nM (each) OXT plus AVP or individually administering these peptides elicited strong (ΔF/F ∼500-600%) responses in VMHvl Esr1 cells (Figure 1Fii and Supplemental Figure S1F-G). These findings demonstrated the presence of functional AVP and OXT receptors in VMHvl Esr1 neurons, consistent with prior electrophysiological studies in mice and guinea pigs 71,72 . Furthermore, it established a system for evaluating cellular responses to OXT and AVP following CRISPR/Cas9 based mutations of their receptors.…”
Section: Resultssupporting
confidence: 90%
“…The oxytocin receptor is a Gq coupled receptor and expressed highly in the VMHvl (Young et al, 1997 ; Gould and Zingg, 2003 ) ( www.brain-map.org , experimental ID: 75081001). In vitro slice recording showed that oxytocin can directly excite VMHvl cells when bath applied (Inenaga et al, 1991 ). The source of oxytocin to the VMHvl is not clear.…”
Section: Molecular and Circuit Mechanisms For Driving Aggression-relementioning
confidence: 99%
“…The mediobasal hypothalamus (MBH) has been identified as an important site for the feedback action of sex steroids on sexual receptivity and the luteinizing hormone surge in both the rat (9) and the sheep (10). This brain region also contains OXY receptors in rodents (1 1,12), and OXY infusions into this site in rats stimulate both neuronal activity (13) and female sexual receptivity (5,7). Oestrogen treatment also increases the number of OXY receptors in the MBH (11).…”
mentioning
confidence: 99%